O papel da IL-18 na infecção por Leishmania amazonensis - Caio Cotta Natale (2015)
In infection by Leishmania amazonensis the classic model of Th1 and Th2 polarization, found in the model of infection with Leishmania major, does not apply. A mixture of responses not fitting the profiles of susceptibility and resistance is observed. IL-18 is a pro-inflammatory cytokine that has a dubious role. It polarizes T lymphocytes to theTh1 phenotype because it has the ability to induce the production of IFN- by NK cells and T lymphocytes. However, depending on the environment, it can induce a Th2 phenotype. Our work aims at identifying the role of IL-18 in the course of infection and development of skin lesions in mice infected by L. amazonensis. Our data showed that the wild-type animals (C57BL/6) have larger lesions than those of IL-18 KO since the beginning of the infection. In addition, at the times analyzed, the two strains have the same parasite burden. We found considerable levels of IL-4, IFN-, TNF and IL-10 in lesions, demonstrating that there is no polarization of T helper cells to a specific response type. Analyzing the cellular profile, we noted that the wild-type lesions tend to have a larger population of inflammatory cells, such as NK cells, monocytes, macrophages and neutrophils. There were more neutrophils at the eight week of infection in wild-type mice, which coincided with increased presence of necrotic tissue in the skin. We have also seen that bone marrow-derived macrophages do not express significant levels of IL-18 receptor in face of various stimulations. Macrophages from IL-18 and wild type mice were equally susceptible to infection with L. amazonensis. However, during the course of infection we identified a massive percentage of T cells CD4+ and CD8+ expressing the receptor for IL-18 after the fourth week of infection. This coincides with the appearance of the exacerbated lesion in wild-type mice and can be associated with the peak production of IL-18 seen by ELISA. Our data suggests that IL-18 is partially involved in susceptibility to infection by L. amazonensis. This is likely due to the interaction of IL-18 with T lymphocytes, and, perhaps, its involvement in cell migration and maintenance of the inflammassome pathway, preventing activation of the pyroptosis.